Defining physiological contributions to yield loss in response to irrigation in cotton. (27th October 2020) - Ermanis, Alessandro; Gobbo, Stefano; Snider, John L.; Cohen, Yafit; Liakos, Vasileios; Lacerda, Lorena; Perry, Calvin D.; Aaron Bruce, Matthew; Virk, Gurpreet; Vellidis, George
Abstract: Excessive irrigation can reduce cotton yield, but studies assessing the relative contribution of component physiological processes to yield loss are limited. The objective of the current experiment was to quantify irrigation‐induced yield loss attributable to Intercepted Photosynthetically Active Radiation (IPAR), Radiation Use Efficiency (RUE) and Harvest Index (HI). For three irrigation treatments (well‐watered, over‐irrigated, and dryland) during the 2018 and 2019 growing seasons, biweekly measurements of predawn leaf water potential (ΨPD ) and light interception were taken along with measurements of biomass, lint yield, fibre quality and harvest index. Irrigation effects on yield were only observed during the 2019 season, and the results showed that ΨPD remained relatively high in both seasons and was rarely affected by irrigation treatment. A significant reduction in yield was observed for irrigated treatments, despite the dryland producing lower biomass. Any positive effects of IPAR and RUE on lint yield due to excess irrigation were offset by large declines in HI. We conclude that HI was the dominant contributor to yield loss due to excessive irrigation because reduced boll numbers and average boll mass were observed in plots with the greatest total above‐ground biomass.